Children with sickle cell disease: are they protected from serious COVID-19? - Shahin, Walaa Aboulkasem; Aldeeb, Hayam; Alsulami, Majed; Tammas, Abdullah; Albatniji, Fatma; Almanea, Aljawhara; Zayed, Abdalla Mohamed; Alabbas, Fahad; Alzahrani, Azzah; Bin Ali, Tahani; Elyamany, Ghaleb; Almaghrabi, Rana Hassan; et al. (Frontiers in Pediatrics, 2024)
COVID-19, the pandemic that hit the world in 2020, resulted in millions of deaths, with the elderly and adults dying more often than children. However, the presence of underlying morbidities increased the risk of death. Sickle cell disease (SCD) was previously classified as a major risk factor for severe COVID-19 disease. However, there are a limited number of studies that identify the clinical course of children with SCD and COVID-19.We conducted a retrospective observational study on children with SCD admitted due to COVID-19 at three different institutions in Saudi Arabia between March 2020 and March 2022. We discussed the demographic and clinical characteristics of patients admitted to the hospital.Seventy-six patients with SCD had PCR-confirmed SARS-CoV-2 during the study period; 50.0% of our patient population were children (6-12) years old. Gender was evenly distributed, with 53.9% girls and 46.1% boys. Symptoms more commonly related to the COVID-19 infection included fever, cough, malaise, and vomiting. Chest X-ray findings were mild and nonspecific, met only in around one-third (28) of the included children. The most common symptoms associated with SCD were vaso-occlusive crisis (47.4%) and abdominal pain (11.8%). The overall general look of most of the patients was reassuring. The median length of hospital stay (LOS) was 4.2 ± 2.7 days. The mean white blood cell count was 11.4±5.2 × 10 9 /L, and the mean hemoglobin level was 8.3±1.5 g/dl. Despite having higher levels of the mean d-dimers, lactate dehydrogenase (LDH), and ferritin, it didn't affect the clinical outcome. All recruited patients received hydroxyurea as maintenance therapy. The outcome of our study was reassuring, with no significant morbidity or mortality observed among the recruited patients.Despite SCD being a chronic disease with known specific complications, there has been a claim that COVID-19 infection adds an added risk. The results of this study suggest that the overall outcome of COVID-19 was favorable, with no reported mortality. Further research is needed to understand the factors that contributed to this favorable outcome. In children with SCD, it is still questionable whether hydroxyurea is one of the protective factors against severe COVID-19.Validation through large-scale research is recommended.